MUSCULAR STRENGTH OF FIREFIGHTERS IN THE CITY OF CERES: AN EXPERIENCE REPORT (CIPEEX, 2026)
Introduction: This experience report describes a practical activity carried out with members of the Ceres-GO Fire Department, promoted by academics from the Physical Education course. The proposal sought to integrate theory and practice through the application of physical tests and the development of specific training programs. Objective: To report on the experience gained during the application of localized muscle endurance tests on firefighters in Ceres-GO, integrating academic theory and practice. Methods: This is an experience report on activities carried out at the fire station, with the participation of four professionals, aged between 18 and 59 years. Physical tests for muscular endurance were applied: one-minute sit-ups and one-minute push-ups, following the protocols of the American College of Sports Medicine (ACSM). Results: All firefighters demonstrated good physical conditioning and adequate technique in performing the tests. After the assessment, the academics developed personalized training programs, prioritizing the strength of the abdominal muscles and upper limbs, respecting the principles of physical training and the participants' operational routine. Conclusion: The experience was positive for both the academics and the firefighters, highlighting the importance of physical assessment for health and professional performance. As a suggestion for future actions, it is recommended to increase the number of participants and include the analysis of other components of physical fitness.
Keywords: muscle endurance; physical fitness; firefighters